A framework for knowledge – Driven CRM - Goon, Tuck Choy; Ian, Chai (2004)
In this paper we propose a framework to combine KDD (Knowledge Discovered in Databases) and CRM (Customer Relationship Management), with an emphasis on customer retention. The key aspect of the proposed framework is to enable adaptive use of knowledge discovered to predict customer buying patterns and capture interesting knowledge about customers.